Odpowiedzi

2010-01-10T17:14:43+01:00
A)
2x + 3y = 0.5
3x + y = -1

2x + 3y = 0.5
y = -1 -3x

2x + 3 * (-1 -3x) = 0.5
y = -1 - 3x

2x -3 - 9x = 0.5
y = -1 - 3x

-7x = 3.5 / : (-7)
y = -1 - 3x

x = -0.5
y = -1 - 3 * (-0.5)

x = -0.5
y = -1 + 1.5

x = -0.5
y = 0.5

b)
2x+y=14
8x+1/2y=35 /* -2

2x + y = 14
-16x - y = -70

-14x = -56 /: -14
2x + y = 14

x = 4
(2 * 4) + y = 14

x = 4
8 + y = 14

x = 4
y = 14 - 8

x=4
y = 6

c)
3x+4y=2 /* 5
5x+7y=1 / * -3

15x + 20y = 10
-15x - 21y = -3

-y = 7 / * -1
3x + 4y = 2

y = -7
3x + (4 * -7 ) = 2

y = -7
3x - 28 = 2

y = -7
3x = 30 / :3

y = -7
x = 10


2 1 2